Travma, ideologije pripadnosti, nacija - Starman, Hannah (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
TRAUMA, IDEOLOGIES OF BELONGING, NATION: TOWARDS A THEORETICAL MODEL OF A CULTURE-BUILDING TRANSMISSION OF MASS VIOLENCE. The author analyses the impact of massive traumatisation on emergence and (trans)formations of identity claims (all the way to the processes of ethnicity) through a combination of research results stemming from both clinical psychiatric practice and social scientific theoretical investigations. In the first part, the article focuses on the nature and the structure of trauma and its immediate impact on both the victim's self-understanding and her perception of the surrounding environment. Using the example of the Holocaust survivors and their offspring,the second part proposes an explanatory model for the mechanism of vertical i.e. intergenerational transmission of trauma. The author relies on the results obtained in clinical psychological practice through treatment of dysfunctional families, especially on the narcissist family model developed by psychologists and therapists Stephanie Donaldson-Pressman and Robert M. Pressman. On the basis of the research conducted by sociologist Kai Erikson indisaster stricken communities and using the example of the Jewish community in Israel, the author analyses the dynamics of social relations which emerge as a result of massive traumatisation, especially those segments that form and sustain communities on the basis of shared traumatic experience, and studies the interaction of such communities with their broader social environment.
Keywords: nacionalizem; nationalism; etnični konflikti; identiteta; množično nasilje; The Holocaust; holokavst; družbena travma; družbeni odnosi